Guidelines for elaborating a pedagogic project for the Medical School: a report of experience - Ariadne da Silva Fonseca; Cilene Costardi Ide; Fábio Luís Peterlini (O Mundo da Saúde)
This study aims at describing the construction of an educational project for teaching in a medical school. This is a report of an experience developed by a group of professionals for elaborating guiding principles for the construction of an educational project. The proposal has as a guiding principle the search for an approach to content and practices that overcomes dichotomies that fragment both the theoretical domain and intervention assistance, that supports a qualified medical performance and efficient action in different contexts.